Synergy Between Law Enforcement Officials and Legal Aid Institutions in Criminal Litigation - Wanto, Eko (Jurnal Terekam Jejak, 2025)
Synergy between law enforcement officials and legal aid institutions is crucial for realizing a just, transparent, and community-friendly justice system. Although they have distinct roles, their collaboration complements each other. Law enforcement officials, including the police, prosecutors, and courts, are primarily responsible for enforcing the law, maintaining order, and ensuring that legal proceedings proceed according to procedure. Their role focuses on the formal and procedural aspects of the law. Legal aid institutions play a role in providing access to justice for the poor and vulnerable. Legal aid institutions provide legal assistance, advocacy, and legal education to ensure citizens' rights are protected, especially in complex legal processes. Synergy between law enforcement officials and legal aid institutions is not about replacing each other's roles, but rather about building constructive cooperation. Collaboration between law enforcement officials and legal aid institutions can include joint outreach regarding the rights of suspects, victims, or witnesses to prevent them from becoming victims of injustice. While this synergy is ideal, its implementation often faces challenges, such as lack of communication, differing perspectives, or even allegations of criminalization. Synergy between law enforcement officers and legal aid institutions is an important foundation for building a strong legal state, where every citizen receives equal treatment in the eyes of the law.